Influence of Design Thinking in Art and Design Majors on Cultivating College Students’ Creativity - Gao, Guozhen; Jeong, Dubae (Journal of Educational Research and Policies, 2024)
This study aims to explore in depth how the design thinking of college students majoring in art and design has a profound and lasting impact on creativity. This study comprehensively reveals the positive role of design thinking in multiple dimensions, including stimulating innovative thinking, promoting the improvement of practical operation ability, and cultivating keen aesthetic ability. Design thinking, as a systematic and creative way of thinking, encourages students to examine problems from multiple perspectives, challenge traditional concepts, and continuously explore new possibilities in artistic creation. Furthermore, this article analyzes how the positive effects brought about by design thinking are subtly transformed into an enhancement of students' creativity in daily life and learning. Design thinking is not limited to professional fields; it can also enable students to more sensitively capture inspiration in their daily lives and face various challenges with a more open and flexible mindset. In addition, the multiple factors that affect the cultivation of design thinking, such as educational resources, teaching methods, and personal learning habits, are discussed in depth, and targeted training strategies and suggestions are proposed. These strategies aim to help art and design students develop their design thinking more effectively, thereby promoting a leap in their overall creativity and laying a solid foundation for their future careers.